ZANGEZUR CORRIDOR: REALITIES AND PERSPECTIVES FOR NAKHCHIVAN’S ECONOMY - Shahin Aliye (International Journal of Innovative Technologies in Social Science, 2024)
The article examines the factors that will affect the economy of Nakhchivan with the opening and operation of the Zangezur corridor. Research has revealed that with the implementation of the Zangezur corridor, Nakhchivan will first and foremost emerge from the blockade, gain direct connection with mainland, Azerbaijan, and see an increase in its economic potential. Secondly, with the launch of this corridor, Armenia will also establish its relations with Turkey and Europe through this railway. It can be seen from the studies that were conducted that the Zangezur corridor is of great economic and political importance. One of the issues that increase the political and economic importance of the road is that it is located in one of the main centers connecting East and West. Second, the realization of the Zangezur corridor will create an alternative passage with the main territory of Azerbaijan and the Nakhchivan Autonomous Republic, which is of great importance within the framework of the regional political configuration, which will reduce the impact of the "Nakhchivan transit" issue, which is one of Iran’s most important levers on Azerbaijan. In general, this road will be quite important in the field of both cargo and passenger transportation, which is one of the issues that justify the relevance of the topic. The purpose of the topic is to analyze Zangezur Corridor’s potential for economic impact and development directions, as well as development perspectives. One of the tasks set to achieve the stated goal is to examine the perspectives of activity regulation and sustainable development, the sustainability and development of the additional energy sector.